Religion and Spirituality: Mental Health Arbitrage in the Body of Mosques Architecture - MahdiNejad, Jamal-e-Din (Journal of religion and health, 2020)
Spirituality is a lost human concept and meaning in the universe that is independent of time and place. It is an inclusive concept, which affects everyone. It has also a kind of overlap with the religion; however, unlike the spirituality, religion has potentially a type of certainty and boundaries, and specifically, some adopt it. This meaning implies realities or mental in the objective and concrete world or mental facts in the psyche. The term spirituality and its derivatives, although not being used in the original Islamic texts, is widespread in Muslims literature, both in Persian and in Arabic languages. The past architect being aware of this reality and relying on his beliefs has created a architecture proportionate to his time’s culture and beliefs and using architectural elements and has filled the objective body with the spiritual beliefs. The research shows that the religious beliefs and spiritual practices prevent the spiritual and physical, as well as mental, illnesses and, at the same time, reduce the recurrence of the diseases and their symptoms. On the other hand, it accelerates the recovery rate and increases the probability of returning to the initial state.